The Association between Early Arterial Oxygenation and Mortality Post Cardiac Surgery. Issue 6 (November 2014) - Sutton, A. D. J.; Bailey, M.; Bellomo, R.; Eastwood, G. M.; Pilcher, D. V.
Many studies have been conducted to investigate the relationship between hyperoxia and mortality in cohorts of intensive care unit (ICU) patients with varied and often contradictory results. The impact of early hyperoxia post ischaemia remains uncertain in various ICU cohorts. We aimed to investigate the association between arterial oxygenation (PaO2 ) in the first 24 hours in ICU and mortality in patients following cardiac surgery, using a retroespective cohort study of data from the Australian and New Zealand Intensive Care Society adult patient database. Participants were adults admitted to the ICU following cardiac surgery in Australia and New Zealand between 2003 and 2012. Patients were divided according to worst PaO2 level or alveolar-arterial O2 gradient in the 24 hours from admission. We defined 'hyperoxia' as PaO2 ≥300 mmHg, 'hypoxia/poor O2 transfer' as either PaO2 <60 mmHg or ratio of PaO2 to fraction of inspired oxygen <300 and 'normoxia' as between hypoxia and hyperoxia. The primary outcome was mortality at hospital discharge. Secondary outcomes were ICU mortality and ICU and hospital length-of-stay. Of the 83, 060 patients 12, 188 (14.7%) had hyperoxia, 54, 420 (65.5%) had hypoxia/poor O2 transfer and 16, 452 (19.8%) had normoxia. There was no association between hyperoxia and in-hospital or ICU mortality compared to normoxia. There was a small increased hospital and ICU length-of-stay for hyperoxic compared to normoxic patients. We concluded that there was no association between mortality and hyperoxia in the first 24 hours in ICU after cardiac surgery.